Preparação do adsorvente magnético geopolímero/ferro metálico para remoção de contaminante orgânico em efluente aquoso - Schadeck Netto, Matias (2019)
In this work the synthesis of a magnetic geopolymer from silica, metakaolin, iron zero-valent, soybean oil, sodium hydroxide and hydrogen peroxide was proposed. The magnetic geopolymer was characterized by X-ray diffraction, Fourier transform infrared spectrometry, surface area, mean pore diameter and pore volume by BET and BJH methods, scanning electron microscopy and vibrating sample magnetometer. The synthesized material was tested as an adsorbent of the anionic dye Acid Red 97 (AR97). The results showed that the magnetic geopolymer is mesoporous, has sufficient magnetization to be removed by action of a magnetic field of the aqueous solution, removes more than 94% of dye in only 20 minutes, and has a high adsorptive capacity of 1814.27 mg g-1 of AR97 at a temperature of 318 K. The magnetic geopolymer presented adsorption capacity very close to the initial one for up to five cycles of use. This adsorbent was synthesized from low cost materials with extremely high adsorption capacity and could be easily separated from the treated liquid effluent.